Manga : sixty years of Japanese comics - Gravett, Paul (New York : Collins Design, 2004)
An accessible introduction to the development and diversity of Japanese comics from 1945 to the present.
Irresponsible pictures : addressing perceptions and prejudices -- Catch up, overtake : the medium, the industry, the market, the profession -- Japanese spirit, Western learning : roots in traditional arts and imported cartoons and strips -- The father storyteller : the life and role of Osamu Tezuka, originator of story manga -- From a darker place : Gekiga or 'dramatic pictures' from pay libraries to newsstands -- Boys are forever : boys' comics as the driving force of story manga -- Through a woman's eyes : the genres and genders of girls' and women's comics -- Developing maturity : the mass market for young males and adult men grows up -- The all-encompassing : a medium for every taste, interest and stage of life -- Personal agendas : the individualism of underground, fanzine and art comics subcultures -- Culture and Imperialism : manga as a major export and global influence.
Bibliografija: str. 172-173 i kazalo.
Keywords: japanski strip -- manga -- povijesni pregled